Inhibitory effects of Saussurea involucrata (Kar. et Kir.) Sch. -Bip. on adjuvant arthritis in rats. (24th December 2016) - Han, Xiaoli; Su, Dan; Xian, Xiaoyan; Zhou, Mingyang; Li, Xianzhe; Huang, Jian; Wang, Jinhui; Gao, Huiyuan
Abstract: Ethnopharmacological relevance: Saussurea involucrate (Kar. et Kir.) Sch. -Bip is an endangered species of the Compositae family, and this species has long been used for the treatment of rheumatoid arthritis, dysmenorrhea, stomachache, and altitude sickness in Uighur folk and Chinese medicine. Aim of the study: This study aimed to investigate the different therapeutic efficacy of alcohol infusion (SEI) and water decoction (SWD) of S. involucrata in treating rheumatoid arthritis using complete Freund's adjuvant (CFA)-induced arthritis (AA) in a rat model. Materials and methods: Male Wistar rats (160–180 g) were immunized by intradermal injection of 0.1 mL of CFA into the left hind metatarsal footpad. Aspirin was chosen as the positive drug. Alcohol infusion (SEI, 400 and 800 mg/kg) and water decoction (SWD, 443 and 886 mg/kg) of S. involucrata aerial parts were orally administered from day 1 and continued for 21 days. Arthritis severity was evaluated by arthritic score, body weight loss, and paw swelling. The levels of TNF- α, IL- β, and IL-6 in the serum of AA rats were detected by enzyme linked immunosorbent assay (ELISA). Histological changes in the ankle joint were also analyzed in the AA rats. Results: Both SEI and SWD significantly ameliorated AA severity, as suggested by the modulatory effects on body weight loss, paw swelling, and arthritic score. Histopathological improvement in the joint architecture was also observed in the SEI- and SWD-treated AA rats. The overproduction of TNF- α, IL-1 β, and IL-6 was remarkably attenuated in the serum of all treated rats. Furthermore, the therapeutic effect of SWD was more potent than that of SEI in treating rheumatoid arthritis using AA in a rat model, which was reported for the first time. Conclusions: These results suggested that the extract of S. involucrata significantly attenuated adjuvant arthritis in rats by decreasing the levels of TNF- α, IL-1 β, and IL-6 in the serum. S. involucrata has the potential to be regarded as a candidate for the treatment of human arthritis. Moreover, the therapeutic effect of SWD was much better than alcohol infusion, indicting that active constituents are mainly in the water extract, which is helpful for the clinical treatments to choose the appropriate process. Graphical abstract: